Evaluation of Green Investment in Renewable Energy Power Plants Using Analytical Hierarchy Process in Archipelago - Ferdy Hidayatullah; Rizki Julia Utama; Muksalmina; Ahmad Syahyana; Sari Raudhatul Jannah SI; Safura Rusydi; Lukman Nul Hakim; Mairezaton; Ismi Ridha Mulyana (CV Edujavare Publishing, 2026)
This study evaluates green investment in solar photovoltaic (PV) power plants in Indonesia’s archipelagic regions using the Analytical Hierarchy Process (AHP). Despite the country’s renewable energy target, solar and wind development remains constrained by investment risks, inadequate infrastructure, and policy uncertainty. The study aims to identify and prioritize the key determinants influencing green investment decisions for solar PV projects in island areas. Data were collected through questionnaires and interviews with 75 government representatives, researchers, and practitioners, with 35 responses meeting the AHP consistency requirement. The results indicate that policy factors are the most influential dimension (0.4825), followed by economic (0.3120) and technical factors (0.2055). At the sub-criteria level, profitability (0.7724), renewables obligation (0.6055), and technological maturity (0.6020) received the highest priorities. The findings show differences among stakeholder perspectives regarding subsidies, regulatory certainty, and financial accessibility. The study contributes a structured multi-stakeholder decision-making model and recommends combining fiscal incentives, long-term regulatory frameworks, and risk-mitigation mechanisms to accelerate solar PV investment.